WATER FOR POWER IN THE TWENTY-FIRST CENTURY: WHAT A GROWING POPULATION, CHANGING CLIMATE, AND ENERGY DEVELOPMENT MEAN FOR UTAH'S WATER RESOURCES (Utah Environmental Law Review; Vol 32 No 2 (2012), 2012)
While water resource challenges are not unique to Utah, a combination of arid climate, rapid population growth, and aggressive governmental pursuit of energy development necessitates a uniquely high level of care in protecting, developing, and planning for the future use of its water resources. The open questions are how to balance supply and demand, and whether existing legal and policy institutions will lead to socially optimal outcomes. The importance of prudent water management is underscored by projected future demands on Utah’s water resources. Utah’s population is projected to grow at almost twice the rate of the United States as a whole, and more rapidly than that of all but four other states. Utah’s new residents, as well as the goods and services they produce and consume, will all require water. Non-consumptive value such as instream flows, sensitive species, and aesthetics will compete for water against traditional consumptive uses. In addition, a changing climate is likely to reduce snowfall, increase fluctuations in precipitation, increase evaporation, and otherwise impact water availability. Recent water and energy development proposals arise against this backdrop and will force hard choices regarding the management of Utah’s finite water resources.